Improving the biological function of decellularized heart valves through integration of protein tethering and three‐dimensional cell seeding in a bioreactor. (18th December 2017) - Namiri, Mehrnaz; Kazemi Ashtiani, Mohammad; Abbasalizadeh, Saeed; Mazidi, Zahra; Mahmoudi, Elena; Nikeghbalian, Saman; Aghdami, Nasser; Baharvand, Hossein
Abstract: Decellularized xenogeneic heart valves (DHVs) are promising products for valve replacement. However, the widespread clinical application of such products is limited due to the risk of immune reaction, progressive degeneration, inflammation, and calcification. Here, we have developed an optimized decellularization protocol for a xenogeneic heart valve. We improved the biological function of DHVs by protein tethering onto DHV and three‐dimensional (3D) cell seeding in a bioreactor. Our results showed that heart valves treated with a Triton X‐100 and sodium deoxycholate‐based protocol were completely cell‐free, with preserved biochemical and biomechanical properties. The immobilization of stromal derived factor‐1α (SDF‐1α) and basic fibroblast growth factor on DHV significantly improved recellularization with endothelial progenitor cells under the 3D culture condition in the bioreactor compared to static culture conditions. Cell phenotype analysis showed higher fibroblast‐like cells and less myofibroblast‐like cells in both protein‐tethered DHVs. However, SDF‐DHV significantly enhanced recellularization both in vitro and in vivo compared to basic fibroblast growth factor DHV and demonstrated less inflammatory cell infiltration. SDF‐DHV had less calcification and platelet adhesion. Altogether, integration of SDF‐1α immobilization and 3D cell seeding in a bioreactor might provide a novel, promising approach for production of functional heart valves.